A study of the behaviour of free gold in flash flotation and gravity recovery - McGrath, Teresa Diane Hayward (Curtin University, 2014)
Gravity and flash flotation are used to recover free gold within the milling circuit, however, this arrangement is poorly understood and consequently, it is difficult to predict circuit performance. Identifying the impact that changes in mineralogy, reagent use, operational factors, and physical variables (size, shape, surface area and elemental composition) will have upon the behaviour of free gold particles will lead to an improved understanding of the behaviour of free gold within the milling circuit.